Implementasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) dan Tantangan Pelayanan Kesehatan: Studi Fenomenologi - Lin Winda; Agus Zainuri; Wahyuti Wahyuti; Yacob Ruru; Septevanus Toding; Arius Togodly (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
This study examines the implementation of the Hospital Management Information System (SIMRS) in improving the quality of healthcare services at Tiom Regional Hospital, Lanny Jaya Regency, a remote area with limited resources and geographical challenges. This research was motivated by the long patient waiting time (±90 minutes from registration to medical consultation) and the suboptimal implementation of SIMRS, which is still combined with manual administrative processes. This study aims to explore the implementation of SIMRS and understand user experiences in supporting healthcare services. A qualitative approach with a phenomenological design was used. Informants were selected purposively and included hospital management staff, healthcare workers, medical records officers, and patients. Data were collected through in-depth interviews, observations, and documentation, then analyzed using thematic analysis. The findings identified four main themes: (1) suboptimal system quality due to technical and network constraints, (2) the ongoing combination of digital and manual administrative systems, (3) the positive impact of SIMRS on service efficiency, and (4) supporting and inhibiting factors related to human resources, infrastructure, and geographical conditions. In conclusion, SIMRS has the potential to improve the quality of healthcare services; however, its implementation remains inconsistent and is highly dependent on infrastructure readiness and user capacity. Strengthening technological infrastructure, improving user competency, and ensuring stable internet access are crucial to optimizing SIMRS implementation in remote areas.